Activation of paraventricular nucleus of hypothalamus 5-HT1A receptor on sodium intake - Villa, Patricia de Souza; de Arruda Camargo, Gabriela Maria Pavan; de Arruda Camargo, Luiz Antonio; Saad, Wilson Abrao (Elsevier B.V., 2007)
Hypothalamic paraventricular nucleus (PVN) has an important role in the regulation of water and sodium intake. Several researches described the presence of 5-HT1 receptors in the central nervous system. 5-HTIA was one of the prime receptors identified and it is found in the somatodendritic and post-synaptic forms. Therefore, the aim of this study was to investigate the participation of serotonergic 5-HT1A receptors in the PVN on the sodium intake induced by sodium depletion followed by 24 h of deprivation (injection of the diuretic furosemide plus 24 h of sodium-deficient diet). Rats (280-320 g) were submitted to the implant of cannulas bilaterally in the PVN. 5-HT injections (10 and 20 mu g/0.2 mu l) in the PVN reduced NaCl 1.8% intake. 8-OH-DPAT injections (2.5 and 5.0 fig/0.2 mu l) in the PVN also reduced NaCl 1.8% intake. pMPPF bilateral injections (5-HT1A antagonist) previously to 8-OH-DPAT injections have completely blocked the inhibitory effect over NaCl 1.8% intake. 5-HT1A antagonists partially reduced the inhibitory effect of 5-HT on NaCl 1.8% intake induced by sodium depletion. In contrast, the intake of palatable solution (2% sucrose) under body fluid-replete conditions was not changed after bilateral PVN 8-OH-DPTA injections. The results show that 5HT(1A) serotonergic mechanisms in the PVN modulate sodium intake induced by sodium loss. The finding that sucrose intake was not affected by PVN 5-HT1A activation suggests that the effects of the 5-HT1A treatments on the intake of NaCl are not due to mechanisms producing a nonspecific decrease of all ingestive behaviors. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: PVN; sodium appetite; 5-HT; 5-HT1A; pMPPV; sucrose